Native T1 mapping in transthyretin amyloidosis. - Fontana, M; Banypersad, S; Treibel, T; Maestrini, V; Sado, D; White, S; Pica, S; Castelletti, S; Piechnik, S; Robson, M; Gilbertson, J; Rowczenio, D; et al. (2014)
The aims of the study were to explore the ability of native myocardial T1 mapping by cardiac magnetic resonance to: 1) detect cardiac involvement in patients with transthyretin amyloidosis (ATTR amyloidosis); 2) track the cardiac amyloid burden; and 3) detect early disease.ATTR amyloidosis is an underdiagnosed cause of heart failure, with no truly quantitative test. In cardiac immunoglobulin light-chain amyloidosis (AL amyloidosis), T1 has high diagnostic accuracy and tracks disease. Here, the diagnostic role of native T1 mapping in the other key type of cardiac amyloid, ATTR amyloidosis, is assessed.A total of 3 groups were studied: ATTR amyloid patients (n = 85; 70 males, age 73 ± 10 years); healthy individuals with transthyretin mutations in whom standard cardiac investigations were normal (n = 8; 3 males, age 47 ± 6 years); and AL amyloid patients (n = 79; 55 males, age 62 ± 10 years). These were compared with 52 healthy volunteers and 46 patients with hypertrophic cardiomyopathy (HCM). All underwent T1 mapping (shortened modified look-locker inversion recovery); ATTR patients and mutation carriers also underwent cardiac 3,3-diphosphono-1,2-propanodicarboxylicacid (DPD) scintigraphy.T1 was elevated in ATTR patients compared with HCM and normal subjects (1,097 ± 43 ms vs. 1,026 ± 64 ms vs. 967 ± 34 ms, respectively; both p < 0.0001). In established cardiac ATTR amyloidosis, T1 elevation was not as high as in AL amyloidosis (AL 1,130 ± 68 ms; p = 0.01). Diagnostic performance was similar for AL and ATTR amyloid (vs. HCM: AL area under the curve 0.84 [95% confidence interval: 0.76 to 0.92]; ATTR area under the curve 0.85 [95% confidence interval: 0.77 to 0.92]; p < 0.0001). T1 tracked cardiac amyloid burden as determined semiquantitatively by DPD scintigraphy (p < 0.0001). T1 was not elevated in mutation carriers (952 ± 35 ms) but was in isolated DPD grade 1 (n = 9, 1,037 ± 60 ms; p = 0.001).Native myocardial T1 mapping detects cardiac ATTR amyloid with similar diagnostic performance and disease tracking to AL amyloid, but with lower maximal T1 elevation, and appears to be an early disease marker.